Improving Science Learning Outcomes through the Application of Discovery Learning Learning Models to Grade V Students of SD Negeri Ayah - Fauziyati, Khikmah (Social, Humanities, and Educational Studies (SHEs): Conference Series, 2020)
The purpose of this study was to improve student learning outcomes in science muple class V elementary schools through the application of the Discovery Learning learning model. The research conducted was a Classroom Action Research (CAR) consisting of three cycles, with each cycle consisting of four stages, namely planning, implementing, observing and reflecting. The implementation of the action uses the Discovery Learning model with a systematics of initial activities, core activities, and final activities. The results showed that the application of the Discovery Learning model resulted in a successful increase in learning outcomes. The percentage of completeness of science learning outcomes has increased which in the pre cycle was 33%, then in the first cycle it became 58.3%, in the second cycle it reached 83.3%, and in the third cycle it reached 92%. Based on the learning outcomes, it can be concluded that applying the Discovery Learning model can improve the learning outcomes of grade V SD Negeri Ayah students.